The effects of n-3 polyunsaturated fatty acids by gavage on some metabolic enzymes of rat liver - Yilmaz, HR; Songur, A; Özyurt, B; Zararsiz, I; Sarsilmaz, M (Elsevier Sci Ltd, 2004)
In this experimental study, the effect of fish n-3 fatty acids was studied on the some important enzymes of carbohydrate metabolism, hexokinase (HK), glucose-6-phosphate dehydrogenase (GOD), 6-phosphogluconate dehydrogenase (6PGD), lactate dehydrogenase (LDH), and malate dehydrogenase (MDH) in rat liver. Wistar albino rats of experimental group (n = 9) were supplemented fish omega-3 fatty acids (n-3 PUFA) as 0.4 g/kg bw. by gavage for 30 days in addition to their normal diet. Isotonic solution was given to the control group (n = 8) by the same way. At 30(th) day, the rats were killed by decapitation under ether anesthesia, autopsied and liver was removed. Spectrophotometric methods were used to determine the activities of above-mentioned enzymes in the liver. The n-3 PUFA caused increases in the activities of HK, G6PD, LDH, and MDH in comparison with control. These increases were statistically significant (P<0.01) except 6PGD activity. As a result, n-3 PUFA may regulate the metabolic function of liver effectively by increasing HK, GOD, 6PGD, LDH, and MDH enzyme activities of rat liver when added in enough amounts to the regular diet. (C) 2004 Elsevier Ltd. All rights reserved.
17th National Biochemistry Congress -- JUN 24-27, 2002 -- Ankara, TURKEY
Keywords: Fish-Oil; Insulin-Resistance; Gene-Expression; Olive Oil; Omega-3-Fatty-Acids; Sensitivity; Increases; Oxidation; Lipids